Analysis of environmental and working conditions in the health of miners from Seridó Paraíbano – Brazil (Research, Society and Development, 2022)
This work aimed to analyze the influence of environmental and work conditions on the health of miners from Seridó Paraibano. Questionnaires were applied to miners and mining companies in that region and a survey of deaths from radon 222-related diseases was carried out in DATASUS for the cities under study, Paraíba and Brazil. Through the responses obtained in the miners' questionnaire, the Pearson correlation coefficient was used to relate the rate of illness due to gastric and respiratory diseases with the use of PPE (Personal Protective Equipment) and the working hours of the miners. Analyzing the rates of illness due to cancer, it was noticed that the numbers of deaths from lung and stomach cancer in the cities evaluated are about twice as high as the rates presented for Paraíba and Brazil. When evaluating the questionnaires, it was noticed that there is resistance from miners to the use of PPE, used by 40% of the miners, despite the companies interviewed providing such equipment following the recommended by NR - 22. Using statistical analysis, it was found that the smaller the amount of PPE used and the longer the daily workday, the greater the chances of developing diseases compromising the health of the miners. The illness due to cancer in the miners interviewed is 27.4%, and of these, 41% have lung cancer. In addition, 55% have gastric and pulmonary diseases. Through the obtained data, it was verified that the miners of this region are subject to the development of occupational diseases that compromise their health, being a reason of public health concern.